Selecting Transport Modes of Railway and Road Based on Tariff and Travel Time - Sinulingga, Tertib; Surayya, Lily (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2015)
Transportation is a movement of people or goods from the origin place to a destination. Regarding this, the writer is interested in studying the selection of transport modes of railway and road based on the transporting tariff and travel time from Bandung and its surroundings to Tanjung Priok port. The research methods the writer uses are applied method and survey. Based on the tariff and the travel time, we can see clearly the market position of transport using train or truck. It can be stated assertively that the weakness of train is its long travel time: the container from industrial centers must be carried using truck, there are discharging/loading processes at Gedebage container terminal (TPK Gedebage), and the frequency of train departure from Bandung to Jakarta is very low.